Studying the Impact of Forest Fires on Soil Degradation Using Geographic Information Systems and Remote Sensing in the Al-Bayer and Al-Basit Region - الغماز فراس; محمد دكة; يونس ادريس (Latakia University Journal -Biological Sciences Series, 2024)
The forest soils and natural vegetation in the Syrian coast have been subjected to clear violations through excessive cutting and artificial and non-artificial fires, which reflected negatively on the properties of those soils that were depleted, especially the fires that occurred in 2020 that turned the coastal mountains into ashes. Based on the upload of two Landsat8 composite satellite images after combining and modifying their ranges to locate the fire without fog or smoke, the first before the fire in July 2020 and the second after the fire in October 2020, fire intensity maps for the Bayer and Basit area were designed to assess areas affected by forest fires. The fire intensity index map was produced and classified based on the classification of fire intensity levels and therefore the burned areas, which constituted a high risk level of 1499.72 hectares from the Bayer and Al-Basit area, while the burned areas that constituted a medium risk level reached 10820.73 hectares. Three soil samples were taken from the burned forests of Zaghrine, Balloran and Ras al-Basit and compared with three soil samples from the same unburned sites. The soil of the sites is rich in organic matter before the fire, while it almost decreased by half after the fire, while the value of the PH we find that it was higher in the burned sites than the unburned sites due to the ash resulting from the burning of vegetation cover over the forest ground, and the percentage of nitrogen in the burned sites does not exceed 0.3%, and the amount of phosphorus in the burned sites was greater than in the unburned sites, and the amount of potassium, calcium, manganese, iron, zinc and copper available after the fire is increasing, and despite all these Increases in cations, fires may also lead to their loss by soil erosion, runoff and element washing, or by ash volatilization.